IMPLEMENTASI METODE CUSTOMER RELATIONSHIP MANAGEMENT PADA ONE STUDIO MUSIK CIAWIGEBANG - Sugiarto S (FKOM UNIKU, 2017)
One Studio Music is one of the music studios which is addressed in Ciawigebang. One Studio Music offers rental of musical instruments and music studios. The system used in One Studio Music is still manually so that the difficulty in managing visitor data and rental studio and musical instrument into a useful information where the data processing is still written in the ledger and the possibility of data may be lost. Therefore the method of problem solving in this research using CRM method. CRM is a business strategy to improve relationships with customers and satisfy customers. In making this CRM using software development method waterfall model and system design using DFD, ERD. And the programming language used PHP and MySQL. In this study, registered customers as members get CRM facilities such as giving point, sms gateway, event discount, and also member can queue the rental of musical instrument if tool status is not available or being borrowed by other member. System tested using Black Box and White Box. By applying the CRM method the company can retain old customers and also bring in new customers. In addition, CRM deals with customers to improve faster access with better quality